Producción de biomasa en el cultivo de Caupi ( Vigna unguiculata l.) a partir de la fijación del C02 con diferentes densidades bajo condiciones de secano en el fundo “Miraflores” - Banda de Shilcayo - San Martín - Chuquizuta Pinedo, Aldo Danilo (2007)
This thesis work was accomplished in the country property Miraflores belonging's space to University National of San Martín, in Low May's, Provincia and Departament San Martín's, Perú. Geographically you coordinate them characterized to show: Length west with 76; Southern Latitude 6. The most suitable density was evaluated for the production of biomass in the caupí cultivation I treatment to quantify the fixation of carbon and by means of the molecular relationship of it formulates it of the photosynthesis, to find the quantity production of CH20, liberation of 02 and the requirement of water far this process. Also, of sorne characteristic biometric of the plant .and the economic analysis of profitability. The statistical design was DBCA with 4 repetitions and 6 treatments, each parcel it was evaluated, whose aftermaths they were analyzed by means of Varianza's Analysis and DUNCAN'S Multiple test. The data meteorological with 88,50 mm is average rainfall. and the temperature varies among the 15 and 34 ° C. The floor shows experimental in presenta class textural franco arenosa, with an organic matter contents of 3,95%. acid pH is 4,20; besides, with half content P205 : 13,0 ppm; bass in K20: 0,09 rneq/100 g, and bass in Ca+Mg: 3,0 meq/100 g the floor it was concluded that the T4 (0,40 m x 0,25 m) obtained after the production analysis of Carbono improve result, obtaining of C with 44, 7525 g; Fixing C02 with 3, 729375 masses; Requiring 9, 1123725 H20's masses; obtaining 5,46726375 masses of CH20 and liberating 5, 12789063 O2/s masses; case contrary T1 had the smaller values. Of the result obtained on the yields grain performance adjusted to the 14% humidity you concludes that if a significant difference exists among treatments, these results fluctuated among 800, 38 Kg. /ha and 607, 12 Kg. /ha, corresponding to the treatments T4 (0,40 m x 0,25 m) and T1 (0, 15 m x 0,25 m), the adult and smaller respectively. The treatments T 4 and T6 highlighted for their biggest ability in yield, among which difference statistic didn't exist. According to the economic benefits it was determined values of positive profitability with the best treatments, as T 4 (0,40 m x 0,25 m) with S /. 188,26 and T6 {0,60 m x 0,25 m) with S /. 335 respectively.